Phenotype of sickle cell disease. Correlation of haplotypes and polymorphisms in cluster β, BCL11A, and HBS1L−MYB. Pilot study - Ropero, Paloma; Peral, Miriam; Sánchez-Martínez, Luis Javier; Rochas, Sara; Gómez-Álvarez, Miguel; Nieto, Jorge M.; González, Fernando A.; Villegas, Ana; Benavente, Celina (Frontiers in Medicine, 2025)
Objective/Background: Sickle cell disease (SCD) is a monogenic disease with a highly variable phenotype depending on the amount of fetal hemoglobin (HbF), the main modulator. Variation of HbF levels among patients is genetically regulated. HbF determines both the phenotype of the disease and the response to treatment with the main drug used, hydroxyurea. The efforts of the researchers have focused on discovering the genetic factors responsible for HbF variation, mainly describing the haplotypes of the β cluster and single nucleotide polymorphisms (SNPs) at three different loci: BCL11A, HBS1L-MYB, and the β-globin cluster. This study aimed to determine the possible correlation between the number of SNPs and haplotypes with higher HbF levels in a cohort of patients with SCD. A positive association could explain why certain haplotypes, such as Senegal or Arab-Indian, show higher HbF levels and less severe disease. Methods: To test this hypothesis, the characterization of haplotypes was performed using the PCR-RFLP technique and genotyping of three SNPs representative of the three loci with the greatest association with HbF variation: XmnI (rs7482144), BCL11A (rs4671393), and HBS1L-MYB (rs9376092). Results: We found more SNPs in haplotypes related to higher HbF than those with less HbF, although only the SNP XmnI (rs7482144) showed a statistically significant association. Conclusions: We found a direct correlation between haplotypes and the number of SNPs. Haplotypes with higher levels of HbF and less severe phenotypes showed a higher number of SNPs. Thus, the Benin and Bantu haplotypes traditionally associated with poor prognosis showed the fewest mutated SNPs.